THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION: STUDY ON THE CUSTOMERS OF MELODIA HOTEL IN POBIEROWO, POLAND - Rofiah, Tazqiyatur; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to examine the effect of Service Quality on Customer Satisfaction at Melodia Hostel in Pobierowo, Noth of Poland, Polandia. The regression analysis, F test and t test, were conducted in order to acknowledge the relationship among the independent variables (tangibility, reliability, responsiveness, assurance, and empathy) on Customer's Satisfaction. This study is explanatory research. 100 questionaire were distribute to Melodia's Hostel guest who were staying for more than two times in tree years. The sampling technique used is purposive sampling and the research instruments were tested using the validity test, reliability test, and classical assumption test. The hypothesis testing used F test and t test in multiple regression analysis. The multiple regression showed that simultaneously and partially Tangibility, Reliability, Responsiveness, Assurance, and Empathy had significant effect on Customer's Satisfaction. The dominant test shows that Assurance has dominant effect on customer's satisfaction.Keywords: service quality, tangibility, reliability, responsiveness, assurance, empathy, customer satisfaction.